Learning mathematics in a fun way from home: factors associated with the use of the online platform “Conecta Ideas” - Sugimara, Claudia (2022)
The goal of this paper is to analyze the factors associated with the use of the online platform “”Conecta Ideas”” at home by 4th grade students from public institutions in Metropolitan Lima in 2019. The study is based on a Model Acceptance of Technology (TAM), which predicts the adoption of a technology mediated by the perception of usefulness, perceived ease, and enjoyment. Using a statistical model of multi-level structural equations, it is found that perceived enjoyment is the variable that best predicts the use of the platform. In turn, female students show higher levels of use. Finally, students with greater concern for mathematics show lower levels of use.